Effectiveness of internet-based exercises aimed at treating knee osteoarthritis (iBEAT-OA): a randomized clinical trial - Gohir, Sameer (2021)
Importance Osteoarthritis is a prevalent, debilitating and costly chronic disease for which recommended first-line treatment is underused.